Physiological and Defense Responses of Tea Plants to Elevated CO2: A Review - Ahammed, Golam Jalal; Li, Xin; Liu, Airong; Chen, Shuangchen (Frontiers in Plant Science, 2020)
Rising atmospheric carbon dioxide, an important driver of climate change, has multifarious effects on crop yields and quality. Despite tremendous progress in understanding the mechanisms of plant responses to elevated CO2, only a few studies have examined the CO2-enrichment effects on tea plants. Tea (Camellia sinensis L.), a non-deciduous woody perennial plant, operates massive physiologic, metabolic and transcriptional reprogramming to adapt to increasing CO2. Tea leaves elevate photosynthesis when grown at CO2–enriched environment which is attributed to increased maximum carboxylation rate of RuBisCO and maximum rates of RuBP regeneration. Elevated CO2-induced photosynthesis enhances the energy demand which triggers respiration. Stimulation of photosynthesis and respiration by elevated CO2 promotes biomass production. Moreover, elevated CO2 increases total carbon content, but it decreases total nitrogen content, leading to an increased ratio of carbon to nitrogen in tea leaves. Elevated CO2 alters the tea quality by differentially influencing the concentrations and biosynthetic gene expression of tea polyphenols, free amino acids, catechins, theanine, and caffeine. Signaling molecules salicylic acid and nitric oxide function in a hierarchy to mediate the elevated CO2-induced flavonoid biosynthesis in tea leaves. Despite enhanced synthesis of defense compounds, tea plant defense to some insects and pathogens is compromised under elevated CO2. Here we review the physiological and metabolic responses of tea plants to elevated CO2. In addition, the potential impacts of elevated CO2 on tea yield and defense responses are discussed. We also show research gaps and critical research areas relating to elevated CO2 and tea quality for future study.